Analisis Yuridis Putusan Nomor 29/PDT.SUS-KPPU/2019/PN BLK Terkait Persekongkolan Tender - Asmah Asmah (Universitas Islam Balitar, Blitar, 2023)
Considering the objection to Decision Number 17/KPPU-I/2018 at the Bulukumba District Court which was carried out by business actors to declare null and void or at least cancel the decision Number 17/KPPU-I/2018 in its entirety, it is important to do research to find out the judge's consideration of the tender conspiracy case. Through normative legal research, it resulted that the judgments of the panel of judges in examining and deciding the case Decision Number 29/Pdt.Sus-KPPU/2019/Pn Blk essentially strengthens and takes over all considerations of the ICC Commission Council Decision, however, the panel of judges then decided to reduce the fine from IDR 586,903,909 to IDR 800 million with the judgment that the sanctions imposed by the Respondent against the objected Petitioner have not fulfilled a sense of justice because it was considered too big/unequal compared to the level of the Petitioner's mistake, therefore it is necessary to give the Petitioner sanctions that are more corrective, preventive and educative.